2018
DOI: 10.1002/jnr.24260
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in associations between spatial ability and corpus callosum morphology

Abstract: Rotating mental representations of objects is accompanied by widespread bilateral brain activations. Thus, interhemispheric communication channels may play a relevant part when engaging in mental rotation tasks. Indeed, links between mental rotation and dimensions of the corpus callosum-the brain's main commissure system-have been reported. However, existing findings are sparse and inconsistent across studies. Here we set out to further characterize the nature of any such links, including their exact location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…For example, several studies have shown more strongly lateralized functions in males versus females, including language and visuospatial processes. In particular, females would rely more on interhemispheric communication during tasks involving 3D mental rotation (Kurth et al., 2018), and would show a more bilateral activation of brain areas devoted to linguistic functions (Hausmann, 2016; Kansaku & Kitazawa, 2001; Shaywitz et al, 1995). Bourne (2005) investigated the existence of hemispheric asymmetries during face processing.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have shown more strongly lateralized functions in males versus females, including language and visuospatial processes. In particular, females would rely more on interhemispheric communication during tasks involving 3D mental rotation (Kurth et al., 2018), and would show a more bilateral activation of brain areas devoted to linguistic functions (Hausmann, 2016; Kansaku & Kitazawa, 2001; Shaywitz et al, 1995). Bourne (2005) investigated the existence of hemispheric asymmetries during face processing.…”
Section: Introductionmentioning
confidence: 99%
“…4 ). However, it should be pointed out that the presence of sex differences in the CC is a long-debated issue (Ardekani et al 2013 ; Luders et al 2014 ; Allen et al 1991 ; Prendergast et al 2015 ; Kurth et al 2018 ; Vannucci et al 2017 ; Lee et al 2009 ). In addition, it should be considered that the callosal connections probably have both excitatory and inhibitory functions (Bloom and Hynd 2005 ), so it is not possible to identify a clear relationship between the CC structure and homotopic co-activations.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy fertile women present less asymmetry between the two hemispheres when steroid hormone levels are higher, such as during the luteal phase, and their hand use effect is reduced [ 1 , 10 ]. In healthy women, the midpoint falls mostly in the left half, regardless of the hand used, probably due to a more efficient inter-hemispheric connection than in men, in whom the posterior portion of the corpus callosum is assumed to be less expressed [ 20 , 21 ]. To date, the definite role of estrogens and progestins in the modulation of interhemispheric connections is still unclear.…”
Section: Introductionmentioning
confidence: 99%